THE CHALLENGES OF PREACHING TO POOR WOMEN COMMUNITY (STUDIES OF PREACHING COMMUNICATION TO POOR WOMEN COMMUNITY IN THE TALLO DISTRICT MAKASSAR) - Nur Setiawati; Bisyri Abdul Karim (Al-Qalam, 2021)
This study aims to analyze the access and needs of poor women in the Tallo district in relation to preaching activities. This study used a preaching communication perspective to identify the challenges of preaching strategies and empowering poor women in urban areas. This study used a mixed method between quantitative and qualitative research. The data was collected through literature study, observation, questionnaires, and in-depth interviews. Data analysis used in this study was the interactive model of Miles & Huberman. The results showed that most of the poor women in the Tallo district defined preaching as a lecture and face-to-face activity. They consider that the government should be more responsible for its implementation rather than other organizations or communities. Most of them prefer the theme of worship, family, and morals when dealing with preaching messages. The preferred media for delivering preaching is through lectures and face-to- face compared with electronic and social media.